Implementasi Program Puskesmas Pelayanan Obstetri Neonatal Emergensi Dasar (PONED) di Kabupaten Lebak - Priyono Priyono; Ika Cahyaningrum (Jurnal Akademika Baiturrahim Jambi, 2022)
Maternal Mortality Rate (MMR) is one indicator in looking at existing health problems. MMR in Indonesia is still high. In reducing MMR, the government established a PONED Health Centers (Basic Emergency Neonatal Obstetric Service). The PONED Health Centers must be well implemented to contribute to the reduction of MMR. The purpose of the study was to analyze the implementation of the PONED Public Health Centers in Lebak Regency in terms of input, process, output, and outcome. This research method is qualitative, using a case study approach. The sampling technique used is purposive sampling. The population in this study were 36 PONED Public Health Centers. The sampling technique used is purposive sampling. Participants in the study were the head of the puskesmas and the PONED team from the Rangkasbitung Health Center, Kalanganyar Health Center, Warunggunung Health Center, Bojongmanik Health Center, and Cileles Health Center. In-depth interviews were conducted with ten informants, including representatives from the PONED Core team. In addition to interviews, the data collection process was by filling out checklists and medical record data. The research results found that the human resources of the PONED Health Center have not been fully certified, and the readiness of the service by the 24-hour guard team in 1 day was not optimal; the evaluation of infrastructure facilities in several PONED Centers requires improvement. The evaluation results found that maternal services in several PONED Health Centers still need improvement. The referral system at the PONED Health Center has been running, and the Jamilah program has become an icon of the Bojongmanik Health Center. Some of the conditions that cause MMR are mainly caused by other diseases; the rest are bleeding, hypertension, and blood circulation disorders